Respuesta :
Answer:
y = 3x^2+15x-18
Step-by-step explanation:
Parabola has an equation with one variable in degree 2 and other in degree 1.
Given that y=3(x-1)(x+6) is the function.
y is of degree 1 and x of degree 2
Standard form of these types of parabolas would be
y =ax^2+bx+c.
To make the given equation in standard form, we multiply all factors on the right side
y = 3(x-1)(x+6) = 3(x^2+5x-6)
= 3x^2+15x-18
a=3 b = 15 and c =-18
y = 3x^2+15x-18 is the standard form of the parabola
Answer:
y = 3x^2 + 15x - 18
Step-by-step explanation:
To represent the function y = 3 (x - 1) (x + 6), start by by expanding the equation by multiplying the common factor with each term inside the brackets to get:
y = 3 (x - 1) (x + 6)
y = (3x - 3) (x + 6)
Now multiply both the terms with each other to get:
y = 3x^2 + 18x - 3x - 18
Arrange the like terms together and add them:
y = 3x^2 + 15x - 18
Hence, y = 3x^2 + 15x - 18 is the standard form of the given function.